2000
DOI: 10.1103/physrevb.61.3337
|View full text |Cite
|
Sign up to set email alerts
|

Power dependence of upconversion luminescence in lanthanide and transition-metal-ion systems

Abstract: We show theoretically with the simplest possible model that the intensity of an upconversion luminescence that is excited by the sequential absorption of n photons has a dependence on absorbed pump power P, which may range from the limit of P n down to the limit of P 1 for the upper state and less than P 1 for the intermediate states. The two limits are identified as the cases of infinitely small and infinitely large upconversion rates, respectively. In the latter case, the dependence of luminescence intensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
1,152
4
18

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,986 publications
(1,224 citation statements)
references
References 48 publications
50
1,152
4
18
Order By: Relevance
“…10. As it can be observed, they follow the expected quadratic power dependence, associated to the above described two-photon excitation mechanism [28].…”
Section: J ^7/2supporting
confidence: 67%
“…10. As it can be observed, they follow the expected quadratic power dependence, associated to the above described two-photon excitation mechanism [28].…”
Section: J ^7/2supporting
confidence: 67%
“…The details of this model have already been intensively discussed. 2,16 However, it is worth noting that in this model, the difference caused by the spatial distribution of the donor and accepter might be overlooked since the energy transfer coefficients (W 0 and W 1 ) take the statistically average values. Here the ETU process can be simplified to an energy transfer process View Article Online between two neighboring donor-acceptor ions, which we named as the ''short-range energy transfer model'' in this text.…”
Section: Energy Transfer and Interactionsmentioning
confidence: 99%
“…In the year 2000, Pollnau et al modeled the relationship of excitation density P with upconversion emission intensity I, and found that I p P n under low excitation power density. 16 The value of n indicates the number of NIR excitation photons required to generate one upconversion photon. This popular and distinct description is based on a simplified upconversion picture and a low density excitation assumption.…”
Section: Important Factors For Etu Processmentioning
confidence: 99%
“…5. For the unsaturated UC process, the number of photons which are required to populate the upper emitting level can be obtained by relationship (1) [21]:…”
Section: Up-conversion Luminescence Mechanismmentioning
confidence: 99%